LECTURER-STUDENT TRANSACTIONAL DISTANCE DURING ONLINE LEARNING - Mutohhar Mutohhar; Agung Dwi Nurcahyo (JURNAL ILMIAH BAHASA DAN SASTRA, 2022)
Distance learning has recently been implemented by most universities in Indonesia along with the pandemic situation. Challenges in learning and teaching have been following up during the implementation of distance learning including the emergence of communication gap or distance between lecturers and students, which is popularly known as transactional distance. The study aimed to describe the presence of lecturer-student transactional distance in terms of lecturers’ teaching reflection of their satisfaction towards online learning activities. By conducting a survey to 12 lecturers from different educational institutions and referring to the theory of Transactional Distance of Michael G. Moore, the study found that transactional distance occurred during online learning indicated by several aspects, i.e., (1) the existence of psychological gap in the course, (2) non-existence of interactive communication between lecturer and student, and (3) high rigidity of course structure.